A Holistic Model of Organizational Trust with the Approach of Professional Ethics in Iranian Health System: A Case Study of the Universities of Medical Sciences in Iran - Mohammad Hossein Kashefi; Nader Bohlooli; Karim Eskandari; Hossein Emari (Research and Development in Medical Education)
Background: Given the growing significance of trust and professional ethics within modern organizations, particularly in universities of medical sciences and educational institutions tasked with safeguarding public health, this study aimed to introduce an inclusive organizational trust model utilizing a professional ethics framework within the healthcare system. Methods: The research method of this study was a cross-sectional survey of 240 managers, experts, and employees of the health system. The data collection tool was a questionnaire whose validity and reliability have been checked and confirmed using relative content validity ratio (CVR), content validity index (CVI), and Cronbach’s alpha. To analyze the data, confirmatory factor analysis and structural equation model with partial least squares (PLS) were used to test the model. Results: Based on the research findings (44.7%), the indicators related to cultural and ethical standards (R2=0.742), internal organizational standards (R2=0.689), organizational consequences (R2=0.758), and social consequences (R2=0.690) accentuate the desirability of endogenous structures within the model. The analysis revealed that all factor loadings’ t-values exceeded 1.96 at the 95% confidence level. Hence, a substantial association between manifest variables (concepts) and latent variables (categories) was established, with all factor loadings being validated. Specifically, environmental factors demonstrate the strongest influence on cultural and ethical standards (t=6.210), while structural domains exert a considerable effect on inter-organizational standards (t=4.614). Notably, inter-organizational standards exhibit the most substantial impact on both social consequences (0.407, t=6.813) and organizational outcomes (0.405, t=3.941). Overall, the findings demonstrated a positive and statistically significant impact of causal conditions on the central phenomenon, contextual, intervening, and central conditions on organizational strategies, as well as strategies on the outcomes of organizational trust within a framework of professional ethics in the healthcare sector. Conclusion: More attention and application of causal factors, contextual factors, intervening factors, and central factors increase the category of trust and professional ethics in organizations, especially the universities of medical sciences and medical training centers.